The role of nanohydroxyapatite on the morphological, physical, and biological properties of chitosan nanofibers - Sato, Tabata P. [UNESP]; Rodrigues, Bruno V. M.; Mello, Daphne C. R. [UNESP]; Münchow, Eliseu A.; Ribeiro, Juliana S.; Machado, João Paulo B.; Vasconcellos, Luana M. R. [UNESP]; Lobo, Anderson O.; Bottino, Marco C.; Borges, Alexandre L. S. [UNESP] (Springer Nature, 2021)
Objectives: This study aimed to evaluate the effects of nanohydroxyapatite (nHAp) particles on the morphological, chemical, physical, and biological properties of chitosan electrospun nanofibers. Materials and methods: nHAp particles with a 1.67 Ca/P ratio were synthesized via the aqueous precipitation method, incorporated into chitosan polymer solution (0.5 wt%), and electrospun into nHAp-loaded fibers (ChHa fibers). Neat chitosan fibers (nHAp-free, Ch fibers) were used as the control. The electrospun fiber mats were characterized using morphological, topographical, chemical, thermal, and a range of biological (antibacterial, antibiofilm, cell viability, and alkaline phosphatase [ALP] activity) analyses. Data were analyzed using ANOVA and Tukey’s test (α = 0.05). Results: ChHa fibers demonstrated a bead-like morphology, with thinner (331 ± 110 nm) and smoother (Ra = 2.9 ± 0.3 μm) distribution as compared to the control fibers. Despite showing similar cell viability and ALP activity to Ch fibers, the ChHa fibers demonstrated greater antibacterial potential against most tested bacteria (except for P. intermedia), and higher antibiofilm activity against P. gingivalis biofilm. Conclusions: The incorporation of nHAp particles did not jeopardize the overall morphology, topography, physical, and biological characteristics of the chitosan nanofibers. Clinical relevance: The combination of nHAp particles with chitosan can be used to engineer bioactive, electrospun composite nanofibers with potential applications in regenerative dentistry.
Keywords: Antimicrobial; Chitosan; Electrospinning; Regeneration; Regenerative dentistry; Scaffolds